2020
DOI: 10.4274/balkanmedj.galenos.2020.2020.4.68
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylmetacrylate Cement Augmentation of the Coccyx (Coccygeoplasty) for Fracture: A Case Report

Abstract: Background: Coccydynia is a painful condition of the sacrococcygeal region, with symptoms associated with sitting and rising from a seated position. It is frequently related to trauma and idiopathic causes, and the pain is mostly chronic. Percutaneous vertebroplasty and sacroplasty are the methods that are widely used for treating compression fractures and sacral insufficiency fractures, respectively. However, the success of polymethylmethacrylate injection in the treatment of osteoporotic coccyx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The surgical approach described herein differs from the previous case reports of coccygeoplasty, as it uses a single-needle technique introducing the PMMA through the midline into the sacrococcygeal axis 14 15. No problems were encountered using this midline needle placement approach in relation to the central spinal canal.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The surgical approach described herein differs from the previous case reports of coccygeoplasty, as it uses a single-needle technique introducing the PMMA through the midline into the sacrococcygeal axis 14 15. No problems were encountered using this midline needle placement approach in relation to the central spinal canal.…”
Section: Discussionmentioning
confidence: 97%
“…Coccygeoplasty (CP) consists of the percutaneous injection of polymethylmethacrylate (PMMA) cement into the sacrococcygeal segments. To our knowledge, only two case reports have been published about CP 14 15. Although it might be a relatively new treatment for coccydynia related to coccygeal hypermobility, injection of PMMA has been widely used in the treatment of pain for vertebral fractures 16 17…”
Section: Introductionmentioning
confidence: 99%
“…Alone with local corticosteroids or local anesthetics, it can be applied both locally to the pericoccygeal area or directly to unstable coccygeal insertion or bone spur. 6,26,27 In cases with a response to the treatment, repeated injection can be performed at intervals. It has been reported that pain control can be achieved only by applying injection in 59% of the cases, and the success rate reaches to 85% in cases where injection and manipulation are combined.…”
Section: Medical Treatmentsmentioning
confidence: 99%
“…Coccygeoplasty is an effective alternative in patients with acute-subacute osteoporotic coccygeal fracture in which we see hyperintensity in the STIR sequence on MRI revealing edema in the coccyx. 25,26 This method can be used safely with local anesthesia and has a low risk of complications, especially in patients with osteoporotic fractures. During the procedure, fluoroscopy imaging in antero-posterior and lateral planes should be performed.…”
Section: Medical Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation